Deviant Behavior in Religious Schools: The Interplay of Psychological Safety, Sanctions, and Academic Commitment - Yuarini Wahyu Pertiwi; Erik Saut Hatoguan Hutahaean; Amirul Muminin; Iredho Fani Reza (AL-ISHLAH: Jurnal Pendidikan, 2025)
Despite the moral emphasis in religious-based schools, some students still engage in deviant behavior. Weak social bonds within families, schools, or communities may contribute to this issue. This study examines the roles of psychological safety, sanctions, and academic commitment in preventing deviant behavior. A survey was conducted among 200 students from religious-based schools in Bekasi. Validated instruments measured Deviant Behavior, Psychological Safety, Sanctions, and Academic Commitment. Data were analyzed using correlation, mediation, and moderation analyses. Psychological safety (-0.195) and academic commitment (-0.279) showed significant negative correlations with deviant behavior. A psychologically safe environment enhanced motivation and compliance, while academic commitment reinforced moral values. Sanctions also had a weak negative correlation (-0.186) with deviant behavior, supporting social norms. Psychological safety and sanctions together explained 6.8% of the variance in deviant behavior (R² = 0.068). Mediation analysis revealed that academic commitment mediated the effect of psychological safety on deviant behavior but not that of sanctions. Moderation analysis indicated that sanctions strengthened the impact of psychological safety. Although the correlations were weak, they remained statistically significant, highlighting the importance of psychological safety in fostering positive behavior. Family psychology emphasizes parental influence, while legal psychology underscores the role of fair and consistent sanctions. Integrating psychological safety, academic commitment, and sanctions may help reduce deviant behavior in religious-based schools. Future research should explore interventions to strengthen moral commitment and social bonds.